Development and Clinical Validation of a Rehabilitation Platform for Hip Fracture in Elderly Population - Vanina Costa; Oscar Ramirez; Luis Perea; Alexander Velasquez; Abraham Otero; Eduardo Rocon; Rafael Raya (IEEE, 2022)
Hip fracture is one of the most common traumatisms associated with falls in the elderly, severely affecting the patient’s mobility and independence. In recent years, the use of robotic technology has proven to be effective in gait rehabilitation, especially for neurological disorders. However, there is a lack of research validating these devices for hip fracture in elderly patients. This paper presents the design and evaluation of a novel assistive platform for hip rehabilitation, SWalker, aimed at improving the rehabilitation of this condition. Functional validation of the SWalker platform was carried out with five healthy elderly subjects and two physiotherapists. Clinical validation was conducted with 34 patients with hip fracture. The control group ( $\text {n}=24$ , age $= 86.38± 6.16$ years, 75% female) followed conventional therapy, while the intervention group ( $\text{n}=10$ , age $= 86.80± 6.32$ years, 90% female) was rehabilitated using SWalker. The functional validation of the device reported good acceptability (System Usability Scale >85). In the clinical validation, the control group required 68.09±27.38 rehabilitation sessions compared to 22.60±16.75 in the intervention group ( $\text{p}< 0.001$ ). Patients in the control group needed 120.33±53.64 days to reach ambulation, while patients rehabilitated with SWalker achieved that stage in 67.11±51.07 days ( $\text{p}=0.021$ ). FAC and Tinetti indexes presented a larger improvement in the intervention group when compared with the control group ( $\text{p}=0.007$ and $\text{p}=0.01$ , respectively). The SWalker platform can be considered an effective tool to enhance autonomous gait and shorten rehabilitation therapy in elderly hip fracture patients. This result encourages further research on robotic rehabilitation platforms for hip fracture.